HUBUNGAN RIWAYAT PAJANAN PESTISIDA DENGAN GANGGUAN FUNGSI HATI PADA PETANI DI DESA SUMBEREJO KECAMATAN NGABLAK KABUPATEN MAGELANG - Ronna Atika Tsani; Onny Setiani; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
Pesticides used as the main material for farmers in pest control at Sumberejo Village. Liver is one of the target organs of pesticides. Accumulation of pesticide exposure into the liver caused liver cell disorders. Preliminary study results showed 10 out of 15 farmers who feel complaints such as weakness, pale, nausea, and pain in the upper right abdomen and 6 of 15 farmers showed jaundice on the eyes. The purpose of this study was to analyze the relationship between pesticides exposure and liver dysfunction in farmers at Sumberejo Village Ngablak District Magelang. This research method was an observational research with cross-sectional approach. The population in this study was 110 farmers and through purposive sampling technique obtained the number of samples 43 farmers. Data obtained from laboratory examination, measurement, and interview with respondents. The result of this research showed that farmers with liver dysfunction were 67,4%. The result of chi-square test showed that there was a relationship between working period (p=0.030) and number of pesticides (p=0.001) and there was no relationship between working duration (p=1.000), spraying time (p=1.000), spraying frequency (p=0.952), spraying direction (p=0.385), use of PPE (p=1.000) and cholinesterase level (p=1.000) with liver dysfunction in farmers at Sumberejo Village, Ngablak District, Magelang.From this study can be concluded the working period and number of pesticides were risk factor for liver dysfunction in farmers at Sumberejo Village Ngablak District, Magelang. To prevent further liver dysfunction it is advisable to mix pesticides according to the rules.